2015
DOI: 10.1111/dmcn.12964
|View full text |Cite
|
Sign up to set email alerts
|

Understanding fatigue in paediatric multiple sclerosis: a systematic review of clinical and psychosocial factors

Abstract: AIM Fatigue in children and adolescents with multiple sclerosis (caMS) is currently poorly understood. This review aimed to provide greater insight into this area and direction for future research by evaluating evidence of associations between fatigue and clinical, psychological, and social factors in caMS.METHOD Studies were identified by searching online databases, hand-searching reference lists, and requesting unpublished literature from key authors. Studies that examined fatigue in relation to at least one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 63 publications
(263 reference statements)
4
45
0
Order By: Relevance
“…Canadian studies about childhood MS have highlighted young people's feelings of loss and grief and the challenges integrating treatment regimens and physical limitations into their daily lives (Boyd & MacMillan, ; Thannhauser, ; Thannhauser, Mah, & Metz, ). In addition, quantitative studies have discovered that young people with MS report lower health‐related quality of life (HRQoL) scores (Mowry et al, ) and have suggested that the fatigue they commonly experience may be associated with depression, reduced HRQoL, and lower school performance (Carroll, Chalder, Hemingway, Heyman, & Moss‐Morris, ; Toussaint‐Duyster, Wong, Van der Cammen‐van Zijp, Van Pelt‐Gravesteijn, & Catsman‐Berrevoets, ). To our knowledge, there have been no in‐depth qualitative studies conducted about young people's experiences of living with MS outside of Canada.…”
Section: Introductionmentioning
confidence: 99%
“…Canadian studies about childhood MS have highlighted young people's feelings of loss and grief and the challenges integrating treatment regimens and physical limitations into their daily lives (Boyd & MacMillan, ; Thannhauser, ; Thannhauser, Mah, & Metz, ). In addition, quantitative studies have discovered that young people with MS report lower health‐related quality of life (HRQoL) scores (Mowry et al, ) and have suggested that the fatigue they commonly experience may be associated with depression, reduced HRQoL, and lower school performance (Carroll, Chalder, Hemingway, Heyman, & Moss‐Morris, ; Toussaint‐Duyster, Wong, Van der Cammen‐van Zijp, Van Pelt‐Gravesteijn, & Catsman‐Berrevoets, ). To our knowledge, there have been no in‐depth qualitative studies conducted about young people's experiences of living with MS outside of Canada.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Additionally, fatigue is one of the most common and disabling symptoms of MS, affecting up to 76% of children and adolescents with MS (caMS). 5,6 The evidence to date suggests that fatigue in caMS is unrelated to clinical disease factors or disease modifying treatments, but is consistently associated with depressed mood, impaired school performance and lower quality of life, and may also be linked to impaired performance on some neurocognitive tasks. 5 Despite its impact, fatigue in paediatric MS is poorly understood and under-researched.…”
Section: Introductionmentioning
confidence: 99%
“…3 Fatigue is also one of the most pervasive and disabling symptoms of MS. 18 In caMS, fatigue levels ranging from 9 to 76% have been reported in studies carried out across Europe and North America, with no clear reason for variability in reports. 9 Despite its impact, fatigue is a poorly understood symptom in paediatric MS, for which effective treatments are lacking. A recent systematic review of 12 studies that explored factors associated with fatigue in caMS indicated that fatigue is unrelated to clinical or demographic factors, but is associated with psychosocial factors including depressed mood, impaired school performance and lower quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Some evidence also suggested that fatigued caMS may have impaired performance on some neurocognitive tasks. 9 This systematic review highlighted the paucity of psychosocial factors explored in the context of fatigue, with most studies focusing on associations between fatigue and depressed mood. Few studies have investigated other potentially modifiable psychosocial factors related to fatigue, such as cognitive and behavioural responses to symptoms e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation